Estudo teórico em nanoestruturas de grafeno e BN dopadas com germânio - Oliveira, Leonardo Melo (2020)
In this thesis we perform rst principle calculations to study the structural, electronic and optical properties of germanium-doped BN and graphene nano-layers. Through calculations of structural properties we show that germanium doping requires an additional amount of energy during the process of synthesis of boron nitride and graphene structures. For BN the results indicate the formation of electronic states in the gap region near the Fermi level, and the incorporation of such an impurity atom induces magnetization states in these nanostructures. The calculation of optical properties also indicates a reduction in the energy gap width and a signi cant reduction in optical conductivity, and a small absorption in the infrared and visible light wavelength range. Graphene has always been found to have a null gap with characteristics close to a semi-metal. In both cases for both BN and graphene the results indicate pronounced absorption peaks located in the deep ultraviolet region.